AB0988 BehÇet's disease in a defined area of northwestern spain. (15th June 2017) - Estévez, M; Argibay, A; Lorenzo, R; Freire, M; Fernandez-Martín, J; Gimena, B; Vázquez-Triñanes, C; Rivera, A
Abstract : Background: Behçet's disease (BD) is a multisystemic inflammatory chronic disease. There is a wide variation in the clinical features of BD among geographical groups. Objectives: To determine the demographic and clinical characteristics of BD in a defined area of northwestern Spain (Vigo). Methods: Patients with BD (International Criteria BD) and seen in the University Hospital of Vigo in Spain, from 1994 to 2016, were retrospectively enrolled. Demographic, clinical, treatment and evolution data were recorded and analyzed using SPSS 22.0. Results: Our patients were 26 male and 25 female. The mean age at the onset of the disease was 33±11.95 years (11–62). Oral and genital ulcers were seen in 100% and 84.3% respectively and skin lesions in 88.2%. Ocular involvement occurred in 35.3%, neurological disease in 39.2% and gastrointestinal involvement in 29.4% (the area worst affected was colon and small bowel). Vascular disease was present in 33.3%. See table 1 . Pathergy test was performed in 18 patients (35.29%) and 10 (55.5%) were positives. HLA B51 was studied in only 13 patients (25.5%) and 8 (61.5%) were positives. 62.7% of patients had no cardiovascular risk factors (CVRF), 27.4% were smokers, 7.8% were hypertensive and 3.9% were hyperlipidemic and diabetic respectively. CVRF were not related to thrombotic events (p>0.05). In regard to gender influence, only pseudofolliculitis was significantly more frequent in men (p<0.001). There was a trend for increased prevalence of ocular disease and elevated erythrocyte sedimentation rate/serum C-reactive protein in men, and anemia in women, which, however, did not reach statistical significance. Treatment consisted of corticosteroids (92.2%), colchicine (68.6.%) and another immunosuppressive agent (35.3%). During the disease course 78.4% of the patients had an outbreak, 45.1% initiated or changed to immunosuppressive agent and 19.6% used biological drugs. Most of our patients (92.1%) were admitted to hospital and these constitute an evident bias. Two patients died during the followup period, but only one in relation of BD (upper gastrointestinal bleeding and seizures). Conclusions: Our series has some particular aspects especially the high frequency of gastrointestinal lesions and neurologic involvement. CVRF do not seem to play a role in the development of thrombotic events. Our results confirm the ethnic and geographic variation of BD expression. Disclosure of Interest: None declared